Manifestations of Theatrical Narrative Space in (LAND BORDER) - Ahmed, Hadeel (Al-Adab Journal, 2024)
One of the important phenomena of criticism in this era is the development of literary genres and their intersection. Through the longtime of criticism, calls for adhering to the rules of the literary genre weakened, when writers and critics realized that literary creativity cannot be restricted or limited by borders. Therefore, literary genres began to merge with one another, and the novel in particular influenced all other artistic mediums, including poetry, theater, film, and television, as well as acting as a dominant genre that encompasses all of its subgenres. Especially and to a greater extent with the genre, (theatre) from which many tools were drawn, to form the mechanisms of constructing the narrative scene, its compositions, its production, and to draw everything related to the details of its space. The novel (The Land Borders) by the Iraqi writer (Maysaloon Hadi), published in 2004, has been chosen by the researcher for this study because it is a structural model that covered the tools of theater to reveal, in a theatrical form, the characters, their crisis psychology, and their lost identity, so the events in it were compatible with the types of characters and aligned with the construction of the narrative. And the mechanisms of shaping the scene, with the imaginative reality of the novel, so starting with the words, moving through the literary dialogue, and culminating with the fictitious world, with its tumultuous people, and its fragmented locations and times, where delusion and confusion blended with reality, the upheaval in its tiniest elements was abundantly obvious. What contributed to revealing (the fragmentation of the narrative space) was that this (space) acquired the characteristic of (theatricality), because the novel relied on presenting the narrative, displaying the turbulent events, and revealing the characters in crisis, on several elements, including: the mutual dialogue between the characters, and the narration of the characters with first person pronoun, in addition to the narration of the narrator (multipile selective omniscience), who chose absence in favor of the voices of his characters. He presented the story through the characters’ awareness, memory, and visions, in a way that made its events appear as if they were taking place now in front of the viewer to match the story’s timing. And the narrative; All of this had an influential role in building the narrative scene, and achieving theatricality and visualization, which clearly contributed to revealing the fragmentation and interpenetration of the world of the novel.